Oncological outcomes of dose reductions in cisplatin due to renal dysfunction for patients with metastatic urothelial carcinoma. Issue 5 (9th March 2021) - Murakami, Tetsushi; Kikuchi, Eiji; Ide, Hiroki; Umezawa, Yuta; Takahashi, Takayuki; Izawa, Mizuki; Hakozaki, Kyohei; Shigeta, Keisuke; Ogihara, Koichiro; Kobayashi, Hiroaki; Kanai, Kunimitsu; Maeda, Takahiro; et al.
Abstract: Objective: To investigate whether dose reductions in cisplatin due to renal dysfunction were associated with worse clinical outcomes in metastatic urothelial carcinoma (UC) patients. Patients and methods: One hundred and fifty one metastatic UC patients who received first‐line gemcitabine plus cisplatin (GC) salvage chemotherapy without a previous history of peri‐surgical chemotherapy were included in this retrospective study. Patients with endogenous creatinine clearance of 60 mL/min or more were treated with a full dose of cisplatin, while those with 45‐59 and 30‐44 mL/min were treated with 75% and 50% doses, respectively. Patients were divided into three groups based on the average administered dose of cisplatin of 100% (Group A, N = 43), 99%‐75% (Group B, N = 59), and less than 75% (Group C, N = 49), and therapeutic responses and the toxicity of GC were compared. Results: Complete response rates were 9.3%, 13.6%, and 14.3% in groups A, B, and C, respectively. One‐year progression‐free survival rates were 22.9%, 31.1%, and 36.7% in groups A, B, and C with no significant differences. One‐year cancer‐specific survival rates were 56.1%, 71.1%, and 68.3% in groups A, B, and C with no significant differences. A multivariate Cox's regression analysis showed that the dose of cisplatin was not an independent prognostic factor for disease progression and cancer death. Furthermore, there were no significant differences in the incidence of severe adverse events. Conclusions: Dose reductions in cisplatin due to renal dysfunction did not worsen clinical outcomes for metastatic UC.